2002
DOI: 10.1556/avet.50.2002.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional and M-mode echocardiographic measurements of cardiac dimensions in healthy Standardbred trotters

Abstract: The aim of the study was to establish normal echocardiographic values of healthy Standardbred trotters not published previously. Twenty-three clinically normal horses weighing between 350 and 490 kg were examined in the same manner: first a thorough physical and then detailed echocardiographic examination were performed. Standardised two-dimensional (2D) and guided M-mode echocardiographic imaging techniques were used to measure interventricular septal thickness (IVS), left ventricular internal diameter (LVID)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
0
18
2
3
Order By: Relevance
“…Comparison of echocardiographic measurements in Spanish foals to previously reported values for other equine breeds: LVID, LVFWT, IVST and MV measurements were smaller in the Spanish foals than the values presented for Thoroughbreds [20,31,32] and Standardbreds [1,5,33] older than 20-24 months. In addition to the different age, most of the papers listed above showed data for animals in training.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…Comparison of echocardiographic measurements in Spanish foals to previously reported values for other equine breeds: LVID, LVFWT, IVST and MV measurements were smaller in the Spanish foals than the values presented for Thoroughbreds [20,31,32] and Standardbreds [1,5,33] older than 20-24 months. In addition to the different age, most of the papers listed above showed data for animals in training.…”
Section: Discussioncontrasting
confidence: 50%
“…In fact, it has been demonstrated that an eccentric cardiac hypertrophy occurs in response to race training attributable to an increased diastolic stress and thus, higher heart chambers are expected in the trained Thoroughbreds and Standardbreds horses [31][32][33]. Another reason to explain the differences between breeds in the echocardiographic measurements is the effect of HR, which was almost 2-fold higher in the Spanish foals than in Thoroughbreds and Standardbreds [1,5,32]. Patteson et al [21] demonstrated that bradycardia is associated with increased LVIDs and decreased LVFWTs and IVSTs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Existem vários trabalhos que fornecem valores de referências para as dimensões e índices cardíacos em equinos das raças Puro Sangue Inglês no modo M (Pipers & Hamlin 1977, Lescure & Tamzali 1984, O'Callaghan 1985, Long et al1992, Slater & Herrtage 1995, no modo B (Vöros et al 1991) e em ambas modalidades (Patteson et al 1995), de Sela Francesa no modo M (Lescure & Tamzali 1984), Puro Sangue Árabe em ambas modalidades (Michima 2003, Michima et al 2004, de modo M em cavalos Quarto de Milha (Bonomo et al 2011), cavalos de trote em ambas modalidades (Bakos et al 2002) e em mestiços no modo M (Lightowler et al 2002a(Lightowler et al , 2002b.…”
Section: Introductionunclassified